Quality assessment of systematic reviews on alveolar socket preservation. Issue 9 (September 2016) - Moraschini, V.; Barboza, E. dos S.P.
Abstract: The aim of this overview was to evaluate and compare the quality of systematic reviews, with or without meta-analysis, that have evaluated studies on techniques or biomaterials used for the preservation of alveolar sockets post tooth extraction in humans. An electronic search was conducted without date restrictions using the Medline/PubMed, Cochrane Library, and Web of Science databases up to April 2015. Eligibility criteria included systematic reviews, with or without meta-analysis, focused on the preservation of post-extraction alveolar sockets in humans. Two independent authors assessed the quality of the included reviews using AMSTAR and the checklist proposed by Glenny et al. in 2003. After the selection process, 12 systematic reviews were included. None of these reviews obtained the maximum score using the quality assessment tools implemented, and the results of the analyses were highly variable. A significant statistical correlation was observed between the scores of the two checklists. A wide structural and methodological variability was observed between the systematic reviews published on the preservation of alveolar sockets post tooth extraction. None of the reviews evaluated obtained the maximum score using the two quality assessment tools implemented.